Local species assemblages are influenced more by past than current dissimilarities in photosynthetic activity. Issue 4 (16th October 2018) - Jung, M.; Rowhani, P.; Newbold, T.; Bentley, L.; Purvis, A.; Scharlemann, J. P. W.
Abstract : Most land on Earth has been changed by humans and past changes of land can have lasting influences on current species assemblages. Yet few globally representative studies explicitly consider such influences even though auxiliary data, such as from remote sensing, are readily available. Time series of satellite‐derived data have been commonly used to quantify differences in land‐surface attributes such as vegetation cover, which will among other things be influenced by anthropogenic land conversions and modifications. Here we quantify differences in current and past (up to five years before sampling) vegetation cover, and assess whether such differences differentially influence taxonomic and functional groups of species assemblages between spatial pairs of sites. Specifically, we correlated between‐site dissimilarity in photosynthetic activity of vegetation (the enhanced vegetation index) with the corresponding dissimilarity in local species assemblage composition from a global database using a common metric for both, the Bray–Curtis index. We found that dissimilarity in species assemblage composition was on average more influenced by dissimilarity in past than current photosynthetic activity, and that the influence of past dissimilarity increased when longer time periods were considered. Responses to past dissimilarity in photosynthetic activity also differed among taxonomic groups (plants, invertebrates, amphibians, reptiles, birds and mammals), with reptiles being among the most influenced by more dissimilar past photosynthetic activity. Furthermore, we found that assemblages dominated by smaller and more vegetation‐dependent species tended to be more influenced by dissimilarity in past photosynthetic activity than prey‐dependent species. Overall, our results have implications for studies that investigate species responses to current environmental changes and highlight the importance of past changes continuing to influence local species assemblage composition. We demonstrate how local species assemblages and satellite‐derived data can be linked and provide suggestions for future studies on how to assess the influence of past environmental changes on biodiversity.